2006
DOI: 10.1002/adsc.200600247
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic, Enantioselective Conjugate Addition of Nitroalkanes to Nitroolefins

Abstract: An organocatalytic, enantioselective conjugate addition reaction of nitroalkanes with nitroolefins has been developed under neat conditions without using an organic solvent. The process, catalyzed by a modified Cinchona alkaloid, affords synthetically useful 1,3-dinitro compounds in good yields (70-82 %) with good degrees of enantioselectivity (67-88 % ee).Keywords: asymmetric catalysis; C À C bond formation; Michael addition; organic catalysisThe Michael addition of stabilized carbanions to electron-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Furthermore, heteroaromatic (entry 11) and conjugated aromatic (entry 12) systems can participate in the processes as well. Finally, we probed the structural effect of the nitroalkanes 4 on the conjugate reactions (entries [13][14][15]. It is found that high ees (87-99 %) for both syn and anti diastereomers are obtained, albeit with an only poor dr when nitroethane 4b and nitropropane 4c are exploited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, heteroaromatic (entry 11) and conjugated aromatic (entry 12) systems can participate in the processes as well. Finally, we probed the structural effect of the nitroalkanes 4 on the conjugate reactions (entries [13][14][15]. It is found that high ees (87-99 %) for both syn and anti diastereomers are obtained, albeit with an only poor dr when nitroethane 4b and nitropropane 4c are exploited.…”
mentioning
confidence: 99%
“…[10] Notably, stabilized carbanions as nucleophiles for the conjugate addition to a,b-unsaturated systems, which involve the formation of new C À C bonds, have been intensively studied. Although significant progress has been made for a,b-unsaturated ketone, [11] ester, [12] amide/imide [13] and nitrostyrene [14] substrates, the development of a catalytic method to promote enantioselective conjugate additions of stabilized carbanions to a,b-unsaturated aldehydes has proven to be more challenging. One of the main reasons for this is the greater susceptibility of a,b-unsaturated aldehydes to 1,2-addition reactions as compared to other unsaturated systems.…”
mentioning
confidence: 99%
“…A range of other Michael donors such as nitroalkanes [35], anthrone [36], and N-heterocycles [37] were also shown to be applicable to the above-discussed catalyst system, that is, catalysts bearing a 6 0 -OH group such as 122 and 123. The enantioselective conjugate addition reaction of a range of cyclic and acyclic nitroalkanes 129 with aromatic and heteroaromatic nitroolefins 130 under neat conditions afforded the synthetically useful 1,3-dinitro compounds 131 in good yields (70-82%) and with good degrees of enantioselectivity (67-88% ee) using 122 (10 mol%) [35].…”
Section: Conjugate Addition Of Nitroalkenesmentioning
confidence: 99%
“…The enantioselective conjugate addition reaction of a range of cyclic and acyclic nitroalkanes 129 with aromatic and heteroaromatic nitroolefins 130 under neat conditions afforded the synthetically useful 1,3-dinitro compounds 131 in good yields (70-82%) and with good degrees of enantioselectivity (67-88% ee) using 122 (10 mol%) [35]. However, no reaction occurred in the case of less reactive aliphatic nitroolefins.…”
Section: Conjugate Addition Of Nitroalkenesmentioning
confidence: 99%
“…[7] Wang et al showed that a modified cinchona alkaloid was a useful asymmetric catalyst for the synthesis of 1,3-dinitroalkanes. [8] Subsequently, the Maruoka research group revealed that N-spiro chiral ammonium bifluorides could efficiently catalyze the asymmetric Michael addition with silyl nitronates. [9] Despite these important contributions, the development of new and efficient asymmetric catalytic systems is still an interesting challenge.…”
mentioning
confidence: 99%